CONSTRUCTION AND ENGINEERING LAW IN SOUTH AFRICA: A FUNDAMENTAL GAP IN THE LLB CURRICULUM? (The Pretoria Student Law Review, 2021)
Construction companies throughout South Africa have continuously been active in major projects, the building of new power plants such as Medupi, new road networks, stadiums for the 2010 soccer world cup that was held in South Africa as well as the building of the tunnels and bridges that now host the Gautrain. The extent of communication technology has also seen a growth in recent years and thus calls for further infrastructure by service providers in this area. The environmental conscience of South Africans and many companies in the search for alternative energy sources has also led to a further growth in ‘green’ technology which is more efficient and productive.3 More examples of construction projects include but are not limited to the building of various malls, roads, residential houses, lying out of pipelines, and a number of other engineering feats, etcetera.
Keywords: South Africa; Construction companies; communication technology; environmental conscience; Building and Construction Law; legal practitioners